Design of economic dispatch model for Gencos with thermal and wind powered generators. (June 2015) - Geetha, K.; Sharmila Deve, V.; Keerthivasan, K.
Highlights: Article's objective is to solve ED of Genco with private wind powered generators. Dynamic cost coefficient is computed using fuzzy logic and implemented in dynamic FiT. Impact of dynamic FiT in ED is analyzed with variable wind velocity and power demand. Dynamic FiT instead of Fixed FiT is beneficial to Genco and Wind Power Producers. Proposed method may attract Wind Power Producers hence reduce the fossil fuel usage. Abstract: This paper introduces a new generic equation for the economic dispatch model of power systems, which include conventional generators as well as wind powered generators considering the variable nature of wind velocity and power demand. Objective function of the proposed model presents a major novelty in the economic dispatch modeling, namely: dynamic cost coefficient, which is computed using fuzzy logic considering both the variable nature of wind velocity and power demand. This dynamic cost coefficient is designed to benefit both the Wind Power Producers and Genco. This model allows for one hour ahead of revision of conventional and wind generation unit schedule, using the information of 'Dynamic Feed in Tariff' of total wind powered generation. This methodology is implemented for a simple test system and Genco system. Genco system comprises of ten thermal units and two wind farms. Genetic Algorithm is used to solve the proposed generic economic dispatch model and find the optimal cost of power generation. In addition, the impact of dynamic cost coefficient on the operation cost of the system is analyzed in the simple test system. Simulation result shows that under critical demand situation, 'Dynamic Feed in Tariff' favors reduction of the operating cost of the systems. The result of the simulation done on Genco system shows that this proposed model benefits both Genco and Wind Power Producer.